ANALISIS PERHITUNGAN DENGAN METODE PROFILE MATCHING UNTUK MEMILIH PENERIMA BEASISWA BIDIKMISI - Kelik Sussolaikah; Nabila Payapo; Ramlan Ramlan; Khoirul Islam; Kusrini Kusrini (CAHAYAtech, 2018)
This assessment is experimental by analyzing calculations using the Profile Matching method to select Bidikmisi scholarship recipients. The five types of requirements in the Bidikmisi scholarship rules are implemented into five types of criteria in the manual calculation process to produce an output containing descending priority value ranking information for Bidikmisi scholarship recipients.